Fertility levels and biofertilizers on nutrient concentrations, uptake and quality of groundnut - Sharma, Sheela; Jat, N.L.; Puniya, M.M.; Shivran, A.C.; Choudhary, Shripal (Annals of Agricultural Research, 2014)
A field experiment was conducted during kharif, 2011 to find out the effect of fertility levels and biofertilizers on nutrient concentration and their uptake on quality of groundnut. Results revealed that each successive increase in recommended dose significantly increased phosphorus concentration in kernel, total uptake of N, P and K, oil content in kernel, oil yield (926 kg/ha) and net returns (Rs51261/ha). However, nitrogen and phosphorus concentrations in haulm, protein content in kernel at par with75% recommended dose. Among biofrtilizers, application of Rhizobium, phosphorous solubilizing bacteria (PSB) and vesicular arbuscular mycorrhiza (VAM) being at par with each other, significantly increased nitrogen and phosphorus concentration in both kernel and haulm, total uptake of N, P and K, protein and oil content in kernel, oil yield and net returnsover control. Among biofertilizers, maximum values were recorded with Rhizobium and least with VAM.